2019
DOI: 10.3319/tao.2019.04.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Triggered slip on multifaults after the 2018 Mw 6.4 Hualien earthquake by continuous GPS and InSAR measurements

Abstract: On 6 February 2018 at 23:50 local time, a M w 6.4 earthquake struck eastern Taiwan. We characterize the instantaneous surface ground motion and the permanent displacement induced by this event from continuous GPS data and SAR images within a short time after the mainshock. We use high-rate GPS positioning techniques to obtain epoch-by-epoch positions peak ground displacement to assess potential seismic damage. The maximum coseismic GPS horizontal displacement of about 450 mm trending to the northeast is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The CRF that is responsible for the 1‐ to 2‐cm/year uplift rate of the mountain (Ching et al, 2011; Ching, Rau, & Zeng, 2007; Ching, Rau, Lee, & Hu, 2007; Rau et al, 2008; Yu et al, 1997) was the site of the 2013 M L 6.4 Ruisui and the 2014 M L 5.9 Fenglin earthquakes and has been inferred to be a west‐dipping blind fault (Biq, 1965; Canitano et al, 2015; Chuang et al, 2014; Lee et al, 2014; Shyu et al, 2006; Wen et al, 2016; Wu et al, 2006). The western digging fault was also inferred to correspond to the 2018 Hualien events (Tung et al, 2019; Yen et al, 2019). Based on the findings of past geological and seismological investigations, the CRF can be subdivided into five segments from north to south: Hoping, Fenglin, Yuli, Chulu, and Binlang segments (Chen et al, 2018), as indicated by the blue lines in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The CRF that is responsible for the 1‐ to 2‐cm/year uplift rate of the mountain (Ching et al, 2011; Ching, Rau, & Zeng, 2007; Ching, Rau, Lee, & Hu, 2007; Rau et al, 2008; Yu et al, 1997) was the site of the 2013 M L 6.4 Ruisui and the 2014 M L 5.9 Fenglin earthquakes and has been inferred to be a west‐dipping blind fault (Biq, 1965; Canitano et al, 2015; Chuang et al, 2014; Lee et al, 2014; Shyu et al, 2006; Wen et al, 2016; Wu et al, 2006). The western digging fault was also inferred to correspond to the 2018 Hualien events (Tung et al, 2019; Yen et al, 2019). Based on the findings of past geological and seismological investigations, the CRF can be subdivided into five segments from north to south: Hoping, Fenglin, Yuli, Chulu, and Binlang segments (Chen et al, 2018), as indicated by the blue lines in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…To begin with Tung et al (2019) determined the coseismic deformation of the 2018 Hualien event using the continuous GPS measurements and InSAR analyses and they found that the main deformation is concentrated on the Milun and the Lingding faults. Moreover, they suggested that an unknown west-dipping fault close to the Lingding fault was triggered during the earthquake sequence.…”
mentioning
confidence: 99%
“…Moreover, they suggested that an unknown west-dipping fault close to the Lingding fault was triggered during the earthquake sequence. Tung et al (2019) also obtained 1-Hz GPS positions peak ground displacement to evaluate the earthquake damages of the Hualien area. Wu et al (2019), on the other hand, investigated and re-measured more than 100 benchmarks set up by various agencies by using network RTK.…”
mentioning
confidence: 99%
“…A M L 5.8 earthquake and its aftershocks within 2 days before the 2018 M L 6.3 Hualien earthquake are essentially foreshocks (the yellow star and circles in Figure 9a) and in space distinguishable from the high coseismic slip area. Some studies suggested that the high coseismic slip distribution on the Milun fault may be a triggered fault slip by the 2018 M L 6.3 Hualien earthquake (Lee et al., 2018; Tung et al., 2019). To verify the correlation, we resurveyed the temporal b ‐value in the high coseismic slip area based on an epicenter released by the Real‐Time Moment Tensor Monitoring System (RMT; https://rmt.earth.sinica.edu.tw/) (the red star in Figure 9a).…”
Section: Discussionmentioning
confidence: 99%